Helping science travel further: a behind-the-scenes look at CIAT's first peer-reviewed video publication - International Center for Tropical Agriculture (2011)
A team of entomologists at CIAT is the first in the CGIAR to publish in the world's only peer-reviewed video journal, JoVE. Click for a quick behind-the-scenes glimpse of how they did it.